2014
DOI: 10.1111/1469-0691.12756
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the treatment of Enterococcus faecalis infective endocarditis in Spain in the last 15 years: from ampicillin plus gentamicin to ampicillin plus ceftriaxone

Abstract: The aim of this study was to assess changes in antibiotic resistance, epidemiology and outcome among patients with Enterococcus faecalis infective endocarditis (EFIE) and to compare the efficacy and safety of the combination of ampicillin and gentamicin (A+G) with that of ampicillin plus ceftriaxone (A+C). The study was a retrospective analysis of a prospective cohort of EFIE patients treated in our centre from 1997 to 2011. Thirty patients were initially treated with A+G (ampicillin 2 g/4 h and gentamicin 3 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
87
0
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(108 citation statements)
references
References 37 publications
7
87
0
9
Order By: Relevance
“…However, patients treated with AG had significantly higher rates of adverse events (ie, renal impairment) requiring therapy withdrawal [11]. These findings coincide with a retrospective study of prospectively collected data that evaluated 69 episodes of IE caused by E. faecalis (30 subjects in AG group; 39 subjects in AC group) [12]. Similar to Fernández-Hidalgo and colleagues, the authors did not observe a difference in in-hospital mortality or 1-year mortality between the AG and AC groups, and found that patients on AG had higher rates of treatment-induced renal failure than patients receiving AC.…”
Section: Human Datasupporting
confidence: 75%
See 1 more Smart Citation
“…However, patients treated with AG had significantly higher rates of adverse events (ie, renal impairment) requiring therapy withdrawal [11]. These findings coincide with a retrospective study of prospectively collected data that evaluated 69 episodes of IE caused by E. faecalis (30 subjects in AG group; 39 subjects in AC group) [12]. Similar to Fernández-Hidalgo and colleagues, the authors did not observe a difference in in-hospital mortality or 1-year mortality between the AG and AC groups, and found that patients on AG had higher rates of treatment-induced renal failure than patients receiving AC.…”
Section: Human Datasupporting
confidence: 75%
“…Clinical data have since evaluated the combination of AC against HLAR and non-HLAR E. faecalis IE [6,11,12]. In 2007, Gavaldà et al assessed the efficacy and safety of AC in 21 patients with HLAR, and 22 patients with non-HLAR E. faecalis IE in a multicenter, open-label clinical trial [6].…”
Section: Human Datamentioning
confidence: 99%
“…Po pierwsze, w kilku badaniach kohortowych dotyczących IZW wywołanego E. faecelis, obejmujących setki przypadków, wykazano, że w przypadkach szczepów E. faecalis bez HLAR, ampicylina zastosowana łącznie z ceftriaksonem wykazuje podobną skuteczność co ampicylina podawana łącznie z gentamicyną. Leczenie jest również bezpieczniejsze, pozbawione ryzyka nefrotoksyczności [183][184][185]. Ponadto jest to schemat terapii z wyboru w leczeniu IZW wywołanego przez E. faecalis z HLAR.…”
Section: Enterococcus Sppunclassified
“…Recent data suggest that the combination of ampicillin and ceftriaxone may be effective for IE due to ampicillin-susceptible E. faecalis, particularly in patients with aminoglycoside resistance, or in whom there is concern for nephrotoxicity with an aminoglycoside 164,165 . Vancomycin-resistant enterococcal IE is fortunately rare, but has been successfully treated with linezolid 166 and daptomycin 152 ; If daptomycin is used, high dose therapy may be considered 101 .…”
Section: Organism-specific Considerationsmentioning
confidence: 99%